IDENTIFIKASI FAKTOR PENGHAMBAT PENCAPAIAN KINERJA PETUGAS SURVEILANS KESEHATAN (GASURKES) DALAM UPAYA PENGENDALIAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN TEMBALANG TAHUN 2016 - Herdyawati, Anisa Eris; Cahyo, Kusyogo; Kusumawati, Aditya (Jurnal Kesehatan Masyarakat (Undip), 2017)
Procurement of Dengue Hemorrhagic Fever (DHF) Gasurkes is an selected alternative to help Semarang government to reduce the number of dengue fever. This was done because the number of health workers in civil servants only focused in dengue fever. Although Gasurkes was started in Semarang since 2015, the number of dengue fever hasn't decline significantly yet. Even the number of dengue fever in 2015 to 2016 was increased from 1737 to 1857 cases.This research was aimed to identify the inhibiting factors for achieving Gasurkes performance in controlling dengue fever in Kecamatan Tembalang in 2016. This qualitative research used descriptive approach. By using purposive sampling, this research taken as many as 10 Gasurkes in Kecamatan Tembalang as subjek penelitiant. Data was collected by indepth interview. Data validity was done by triangulation of source as many as 14 people.The results showed that perceptional speed, ability of deductive thinking, communication skill, dynamic strength and stamina, working experience, education level, demographic factors, and superior support are not inhibiting factors for achieveing Gasurkes performance in controlling dengue fever in Kecamatan Tembalang in 2016. While numeracy skills, memory, family support, residential support, and community support in Gasurkes working area are inhibiting factors for achieveing Gasurkes performance in controlling dengue fever in Kecamatan Tembalang in 2016.